An evaluation of teachers’ perceptions of the kbsm music programme in lower secondary schools in Malaysia based on the cipp model / Liau Swee Foong - Liau, Swee Foong (2014)

(untitled)
The purpose of this study is to evaluate the effectiveness of the Integrated Secondary School Curriculum in Malaysia known commonly as Kurikulum Bersepadu Sekolah Menengah (KBSM) for the Lower Secondary Music programme in the lower secondary schools in Malaysia through the perspectives of the music teachers. Besides, this research also investigated the relationships between the different groups of respondents from (i) Peninsular and East Malaysia, (ii) urban and rural school, and (iii) different teaching experience. The design of the study adopts the Context-Input-Process-Product or CIPP model of evaluation developed by Daniel L. Stufflebeam. The Context evaluation investigates the programme objectives and the barriers faced by the teachers in achieving the goals and objectives of the KBSM curriculum. The input evaluation examines the preparedness of teachers in teaching the KBSM curriculum and the aspects of the programme materials. The process evaluation investigates the strategies used by teachers in the process of teaching and learning and its effectiveness; and the classroom assessment practices for KBSM music, finally the product evaluation examines the students’ performance in terms of acquisition of skills and knowledge in the various components of KBSM music and the results of the change in students’ attitudes. The respondents consist of the target-population of music teachers of the schools with KBSM music programme in lower secondary in Malaysia. A total of 142 KBSM music teachers from 14 states and Federal Territory participated in this study. Data were gathered using structured questionnaires, and semi structured interviews were carried out to obtain further information and to validate data gathered from the questionnaires. The statistical analysis of the data collected was performed using SPSS. The study revealed that in the context of the programme, teachers agreed the programme aims and objectives have been moderately achieved. There were various iv barriers that hinder the programme, among them low curriculum status and students lack the fundamental skills to follow fully in the curriculum was most concerned. Findings suggest that the input aspect, such as the teachers’ subject matter knowledge and curriculum supporting resources of the programme need to be enhanced. Collectively, teachers are capable of employing various strategies in their classroom instructions and able to conduct classroom assessment effectively. Overall, students’ acquisition of knowledge and skills was somewhat mediocre, but teachers agreed that KBSM music students demonstrated a good change in values, attitudes and aptitudes. Implications arising from the study highlighted the need for priority on improving and sustaining the status and also the quality of music education in Malaysia.